2023
DOI: 10.3390/plants12020413
|View full text |Cite
|
Sign up to set email alerts
|

New Paradigms in Brassinosteroids, Strigolactones, Sphingolipids, and Nitric Oxide Interaction in the Control of Lateral and Adventitious Root Formation

Abstract: The root system is formed by the primary root (PR), which forms lateral roots (LRs) and, in some cases, adventitious roots (ARs), which in turn may produce their own LRs. The formation of ARs is also essential for vegetative propagation in planta and in vitro and for breeding programs. Root formation and branching is coordinated by a complex developmental network, which maximizes the plant’s ability to cope with abiotic stress. Rooting is also a response caused in a cutting by wounding and disconnection from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 160 publications
0
12
0
Order By: Relevance
“…Several reports suggested that the endogenous NO accumulation has been implicated as being responsible for the development of adventitious root in plants ( Kang et al., 2018 ; Altamura et al., 2023 ). Compared to CK treatment, Cd stress significantly decreased endogenous NO levels during adventitious root development ( Figure 3 ), implying that Cd stress might lead to a significant reduction of adventitious root formation through inhibiting endogenous NO production.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports suggested that the endogenous NO accumulation has been implicated as being responsible for the development of adventitious root in plants ( Kang et al., 2018 ; Altamura et al., 2023 ). Compared to CK treatment, Cd stress significantly decreased endogenous NO levels during adventitious root development ( Figure 3 ), implying that Cd stress might lead to a significant reduction of adventitious root formation through inhibiting endogenous NO production.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of S. sediminicola Dae20 on the root system, characterized by a strong increase in branching and root hairs, is closely related to its ability to influence the hormonal balance of the plant, either through the direct production of auxin in the form of IAA, through the modulation of ethylene levels, or through the production of nitric oxide. Indeed, these molecules are encoded by genes present in the genome of the bacteria [ 20 ] and they are known to influence these processes in plants [ 46 , 47 , 48 ]. Several species of Sphingomonas have been described with these abilities, such as S. LK11 , S. paucimobilis , S. pokkalii [ 18 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is not surprising that the phytohormones within this group show agonistic and synergistic properties with each other. Well-known examples are the positive effects of JA, SL, and BR on ABA [ 371 , 372 , 373 ] or interactions between BR and AUX [ 374 ]. Interestingly, melatonin has been shown to have a positive effect on stress resistance in various crops but it reportedly decreases the level of ABA, a process that is conserved across the different abiotic stresses [ 375 ].…”
Section: Stress and Metabolitesmentioning
confidence: 99%